Trans/sex - Gilreath, Shannon (2011)
In this essay, I provide a Gay liberation analysis of the phenomenon of transsexuality. To do so is to risk being greatly misunderstood — being labelled as transphobic or, perhaps worse, as a gay conservative!”. Nevertheless, transsexuality, in its more modern, politically correct incarnation of transgender,'” has shifted to the center of “gay rights” organizing in ways I find distressing. This crystallized for me during the 2007— 2008 debates over the Employment Non-Discrimination Act. Transsexuals and their supporters rallied to condemn the legislation and its proponents, most notably Congressman Barney Frank.'™ Such action seemed to me particularly hostile to Gay people, given that transsexuals already had/have greater anti-discrimination protections at the federal level than do Gays’. In this and other obvious ways, transsexuality has become increasingly central to “gay rights,” and it is increasingly celebrated as a path to liberation by gay rights leaders and by the postmodern cannon working to rob Gays of Self-possession even before we have it.